Increased Induction of Inducible Nitric Oxide Synthase Expression in Aortae of Type 2 Diabetes Rats - Yuji Takahashi; Tomoyuki Nakano; Ichiro Wakabayashi (Elsevier, 2008)
The aim of this study was to determine whether the pathway of inducible NO synthase (iNOS) in blood vessels is changed by type 2 diabetes. Lipopolysaccharide (LPS)-induced nitric oxide (NO) production and expression of iNOS and effects of LPS on phenylephrine-induced contractile force were compared in aortae isolated from Goto-Kakizaki (G-K) diabetes rats and aortae isolated from control Wistar rats. Both LPS-stimulated nitrite generation and iNOS expression levels were significantly higher in aortae from G-K rats than in those from control rats. Phenylephrine-induced contractile force in the presence of LPS was significantly lower in aortae from G-K rats than in those from control rats, while contractile force in the absence of LPS was comparable in the diabetic and control groups. On the other hand, incubation of aortae in high glucose-containing medium did not affect the LPS-stimulated nitrite accumulation and iNOS expression and the phenylephrine-induced contractile force, regardless of the presence of LPS. These results suggest that LPS-induced NO production through the iNOS pathway is increased and subsequent attenuation of contractile force by excess NO is enhanced in arteries of rats with type 2 diabetes. Keywords:: artery, glucose, lipopolysaccharide, nitric oxide synthase, type 2 diabetes